Integrated Model for Energy and CO2 Emissions Analysis from Thailand's Long-term Low Carbon Energy Efficiency and Renewable Energy Plan - Wongkot Wongsapai (2018)
© 2016 The Authors. Published by Elsevier Ltd. This paper builds the energy demand and supply model from the bottom-up LEAP software and focus on evaluating and providing insights to the long-term energy and greenhouse gas impact from national energy efficiency and alternative energy plan focus from 2015 to 2036 under the 2010 base year. From the results, the energy demand would increase from 84.77 Mtoe in 2015 to 172.29 Mtoe, or 103.24% in 2036. The greenhouse gas emission would decrease from 503.34 MtCO2 in 2036 by 161 and 116 Mt-CO2 from energy efficiency and alternative energy development plan in 2036, respectively. We also found that this mitigation also impacts to the decrease of grid emission factor from 506 in the BAU to 339 and 140 kgCO2-eq per MWh, respectively due to higher renewable energy sources and imported hydro energy. Policy recommendations to deploy both plans are also raised.